Effect of INM on biochemical and postharvest parameters of guava (Psidium guajava) cv. Hisar Surkha - SOURABH; SHARMA, J R; BALODA, SATPAL; VIJAY; SINGH, NIRMAL; PREETI; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during rainy (kharif) and winter (rabi) season of 2018–19 and 2019–20 at the research farm of CCS Haryana Agricultural University, Hisar, Haryana to study the effects of organic amendments and biofertilizers on biochemical and post-harvest parameters of guava fruits (Psidium guajava L. cv. Hisar Surkha). The experiment consisted of 19 treatments in different combinations and levels of RDF with vermicompost, farmyard manure, and biofertlizers were applied. The results revealed that almost all treatments with combined application of organic and inorganic sources of nutrients significantly influenced the biochemical and post-harvest parameters of guava fruits over control of which treatments T16 (RDF 100% + Farmyard manure + Azotobacter + PSB) and T17 (RDF 100 % + Vermicompost + Azotobacter + Phosphate solubilizing bacteria) proved most effective. All treatments had a significant impact on the total soluble solids, acidity, vitamin C, pectin and sugar content of fruit over the course of two years of experimentation. Shelf-life of fruits also increased with integrated use of 100% RDF with vermicompost and biofertilizers. Physiological loss in weight was minimum (9.73 and 18.34%; 9.61 and 18.46% after 4 and 8 days of harvesting) and shelf-life increased (4.74 and 6.85 days) in harvested fruit in T17 during rainy and winter season, respectively. The overall quality of the fruit was higher throughout the winter than during the rainy season. Hence, a portion of chemical fertilizers can be reduced in fertilization of guava plants through the integrated application of different organic amendments with improvement in different quality parameters.